'Actually' again. (21st March 2022) - Stephanou, Yannis
Abstract: Some authors have suggested that, contrary to what is usually thought, 'actually' and similar expressions ('in fact', 'in reality', etc.) cannot effect a return to the actual world when used in a context generated by a different modal operator, and so are quite unlike the actuality operator of modal logic. I argue that they can induce such a return. The argument involves comparing them with other devices that can play a similar role, such as scope and mood, and examining the effect of 'actually' and the like in a range of different sentences.